Intravascular Laser Irradiation of Blood (ILIB) on Sleep Quality Improvement: A Randomized Placebo-Controlled Clinical Trial - Lucas Peres de Sousa; Cinthya Gutierrez Cosme Duran; Raquel Agnelli Mesquita-Ferrari; Kristianne Porta Santos Fernandes; Sandra Kalil Bussadori; Anna Carolina Ratto Tempestinni Horliana; Afonso Shiguemi Inoue Salgado; Lara Jansiski Motta (Journal of Sleep And Sleep Disorder Research, 2026)
Introduction Sleep quality is a fundamental determinant of human health and well-being. Modified Intravascular Laser Irradiation of Blood (ILIB), a non-invasive therapeutic modality, has emerged as a potential intervention for sleep-related disturbances. Proposed mechanisms include reduced blood viscosity and platelet aggregation, activation of superoxide dismutase, increased oxygen bioavailability, enhanced microcirculation, elevated serotonin levels, and decreased cortisol concentrations—physiological processes intricately involved in sleep regulation, mood modulation, and the stress response. Objective To evaluate the effects of Modified Intravascular Laser Irradiation of Blood (ILIB) on sleep quality in individuals with self-reported sleep disturbances. Methods A randomized, placebo-controlled clinical trial was conducted with participants who reported poor sleep quality. Subjects were randomly assigned to one of two groups: the intervention group received ILIB using a 660 nm red laser, while the control group received a placebo treatment (light emission with sub-therapeutic power, <1 mW). Both groups underwent the same treatment schedule. Sleep quality was assessed at baseline and after six treatment sessions using the Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale (ESS). Results Participants in the ILIB group showed statistically significant improvements in the primary outcome of global sleep quality. PSQI scores decreased from 10.24 at baseline to 6.47 post-treatment. ESS scores showed a non-significant change from 10.44 to 10.12. These results suggest enhanced overall sleep quality and reduced sleep latency, although the observed reduction in daytime sleepiness did not reach statistical significance. Conclusion Modified Intravascular Laser Irradiation of Blood appears to be a promising non-invasive approach for improving sleep quality. The clinical outcomes observed are comparable to those reported in both pharmacological and behavioral sleep interventions, particularly in terms of PSQI improvements. These preliminary findings support the need for further research to clarifyunderlying mechanisms, optimize treatment parameters (e.g., dosimetry and duration), and expand outcome assessments to include biomarkers and polysomnographic data.
Keywords: Intravascular Laser Irradiation of Blood